Analysis of Factors for Increased Blood Pressure in Hypertensive Clients at Panarukan Community Health Center, Situbondo Regency - Silvi, Dinia; Andayani, Sri Astutik; Sholehah, Baitus (Research of Service Administration Health and Sains Healthys, 2024)
The prevalence of hypertension or blood pressure in Indonesia is quite high. In addition, the consequences it causes a public health problem. Hypertension is a disease whose number continues to increase every year. It is estimated that the number of hypertension sufferers in the world currently reaches 970 million. Data from the World Health Organization (WHO) in 2015 showed that 1.13 billion people in the world have hypertension. Meanwhile, cases of hypertension in Indonesia in 2018 amounted to 31.4%. The average person who experiences or suffers from hypertension is around 30 to 65 years old and over. In addition, there are many factors that cause patients to develop hypertension. Purpose : to find out the factors that cause increased pressure in hypertensive clients. Methods: This study used a cross-sectional design with a population of 401 hypertensive clients at the Panarukan Health Center, Situbondo Regency. The sampling technique used the slovin formula and obtained a sample of 200 people. Data collection was carried out by means of observation, interviews and questionnaires. The data analysis used was bivariate test with Spearman's rank and multivariate test using logistic regression. This research was conducted at the Panarukan Health Center in Situbondo Regency in June – July 2023. Results: Age has an effect on blood pressure in hypertensive clients with a P Value = 0.000, genetics has an effect on blood pressure in hypertensive clients with a P Value = 0.000), Physical activity has an effect on blood pressure in hypertensive clients with P Value = 0.000, and diet affects blood pressure in hypertensive clients with P Value = 0.000). Age is the most dominant factor related to blood pressure in hypertensive clients. Conclusion: there are 4 influential variables and diet is the most dominant factor on blood pressure in hypertensive clients.